(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The article contains the information about the ecological station in the world and in the mountainous region of Central Asia. It was shown that, the rapid increase of negative anthropogenic impacts in recent years leads more to the destruction of the natural ecosystem. For the effective resolving of the problems the system of functions is regional the realization of which can improve to definition extent the ecological situation and favors the mountainous of ecological balance in the nature. It is also suggested the elaboration and applying the new approaches and conception of the relationships between human and the environment, and also the completion of curriculum and educational programmers with conception of stable improvement and the control over the internal resources’.